Potential of Stem Cell-Based Therapy for Ischemic Stroke - Marei, Hany E.; Hasan, A.; Rizzi, R.; Althani, A.; Afifi, N.; Cenciarelli, C.; Caceci, Thomas; Shuaib, Ashfaq (Frontiers in Neurology, 2018)
Ischemic stroke is one of the major health problems worldwide. The only FDA approved antithrombotic drug for acute ischemic stroke is the tissue plasminogen activator (tPA). The very narrow time window of 3-5 hours required to ensure its effectiveness, but tPA’s potential to exacerbate blood-brain barrier (BBB) leakage (thereby increasing hemorrhagic incidents) necessitates a search for therapeutic alternatives. Stem cell based therapy for ischemic stroke seems to be promising candidate. Several studies have been devoted to assessing the therapeutic potential of different types of stem cells such as neural stem cells (NSC), mesenchymal stem cells (MSC), embryonic stem cells (ESC), and human induced pluripotent stem cell-derived neural stem cells (hiPSC-NSCs) as treatments for ischemic stroke. The results of these studies are intriguing but many of them have presented conflicting results. Additionally, the mechanism(s) by which engrafted stem/progenitor cells exert their actions are to a large extent unknown. In this review, we will provide a synopsis of different preclinical and clinical studies related to the use of stem cell based stroke therapy, and explore possible beneficial/ detrimental outcomes associated with the use of different types of stem cells. Moreover, a list of completed and ongoing preclinical and clinical studies is provided, and their major outcomes are discussed. Due to limited/short time window implemented in most of the recorded clinical trials about the use of stem cells as potential therapeutic intervention for stroke, further clinical trials evaluating the efficacy of the intervention in a longer time window after cellular engraftment are still needed.